Factors Influencing Nerinetide Effect on Clinical Outcome in Patients Without Alteplase Treatment in the ESCAPE-NA1 Trial - Mayank Goyal; Bijoy K. Menon; Johanna Ospel; Mohammed Almekhlafi; Charlotte Zerna; Raul Nogueira; Ryan McTaggart; Andrew M. Demchuk; Alexandre Y. Poppe; Brian Buck; Kathy Heard; Manish Joshi; et al. (Journal of Stroke)
Background and Purpose In the ESCAPE-NA1 (Efficacy and Safety of Nerinetide for the Treatment of Acute Ischaemic Stroke) trial, treatment with nerinetide was associated with improved outcomes in patients who did not receive intravenous alteplase. We compared the effect of nerinetide on clinical outcomes in patients without concurrent intravenous alteplase treatment within different patient subgroups. Methods ESCAPE-NA1 was a multicenter randomized trial in which acute stroke patients with baseline Alberta Stroke Program Early CT Score (ASPECTS) >4 undergoing endovascular treatment (EVT) were randomized to intravenous nerinetide or placebo. The primary outcome was independence (modified Rankin Scale [mRS] score 0–2) at 90 days. We assessed baseline, clinical, and imaging variables as predictors of outcome and for evidence of treatment effect modification. We constructed two multivariable models using variables known prior to randomization and variables known immediately post-EVT procedure to provide adjusted estimates of effect. We assessed for evidence of treatment effect modification using multiplicative interaction terms within each model. Results Four hundred forty-six patients were included in the analysis. Clinical outcomes were better in patients randomized to the nerinetide arm (mRS 0–2: 59.4% vs. 49.8%). There was possible treatment effect modification by ASPECTS score; patients with ASPECTS 8–10 showed a larger treatment effect compared to those with lower ASPECTS score. Younger age, lower NIHSS score, lower baseline serum glucose, absence of atrial fibrillation at baseline, higher ASPECTS score, middle cerebral artery (vs. internal carotid artery) occlusion, use of conscious or no sedation (vs. general anesthesia), and faster treatment were all predictors of favorable outcome. Conclusion Patients in the nerinetide arm who were not treated with concurrent alteplase showed improved clinical outcomes and the treatment effect was larger among patients with favorable ASPECTS profiles.